Phytoestrogenic effect of Inula racemosa Hook f – A cardioprotective root drug in traditional medicine. (10th January 2018) - Kalachaveedu, Mangathayaru; Raghavan, Divya; Telapolu, Srivani; Kuruvilla, Sarah; Kedike, Balakrishna
Abstract: Ethnopharmacological relevance: Roots of Inula racemosa are used as a cardio protective in Ayurveda in India, being prescribed as a medicine for precordial chest pain, cough and dyspnoea, both singly and as a poly herbal. Aim: Evaluation of Phytoestrogenic activity of the root extracts of Inula racemosa and compounds isolated therefrom in vivo, in silico and in vitro . Materials and methods: Alcohol (IrA) and hexane (IrH) extracts characterized by HPTLC/GC-MS analysis respectively and processed for compound isolation were evaluated for estrogenic activity (100 & 250 mg/kg bw) by the Immature rat uterotrophic assay using ethinylestradiol (EE −30 µg/kg bw) as standard drug. Alantolactone (ALT), Isoalantolactone (IALT) and Stigmasterolglucoside (SG) isolated from the extracts were characterized and screened in silico for ERα, ERβ binding affinity, assessed in vitro for growth modulatory effects on MCF-7 cells by MTT assay and cell cycle distribution analysis using Flow cytometry. RT-PCR analysis evaluated the mRNA expression of pS2 in these cells post exposure to ALT, IALT and SG. Results: In the IrA treated groups there has been a statistically significant increase (P < 0.05) in absolute and normalised uterine weight, uterine diameter, endometrial thickness, luminal epithelial cell height, diameter of ovary and in the number of primary and secondary ovarian follicles relative to untreated controls. Presence of ciliated epithelial cells in the oviduct, elevated number of early growing follicles characterized by an increased oocyte diameter, and signs of vascularization in the cortex of ovarian sections in this group relative to EE treated group are indicative of pervasive activation of follicular growth and initiation. Virtual docking demonstrated ERα affinity for IALT, ERβ affinity for ALT, while SG showed a high binding affinity to both with a relatively greater ERβ binding affinity. Dose dependent decrease in cell viability mediated by IALT and SG in the MTT assay is corroborated by a statistically significant increase (p < 0.05) in sub G0-G1 cells by SG at 200 and 400 µM in cell cycle analysis and there has been an induction of pS2 by IALT and SG in the ER regulated MCF-7 cells. Conclusions: Demonstration of classical morphological changes induced by estrogen stimulation mediated by IrA in vivo at both the tested doses, isolation of the antioxidant SG from IrA and its dose dependent growth inhibitory effect on estrogen sensitive MCF-7 cells through apoptotic induction and an up regulation of pS2 are suggestive of an anti-estrogenic effect through estrogen receptor binding affinity, typical of phytoestrogens that bind to ER but do not elicit a full estrogenic response. The observed estrogenic effect of IrA suggests a multi mechanistic molecular action involving antioxidant as well as redox signalling pathways acting in consonance with their anti-estrogenic effects owing to the weak estrogen like competitive receptor binding of SG. Graphical abstract: